S04: Back to a Healthy Society (BASE): Reconnecting and Enhancing Healthy Living in Socially Isolated Older Adults Through a Peer-To-Peer Change Agent Approach (Baltic Journal of Sport and Health Sciences, 2026)
During and in the aftermath of the COVID-19 crisis older people presented significantly reduced practice of physical activity and social contact and were exposed to several psychological stress factors that negatively affected physical and mental health. To change this for the better, the Erasmus+ project ‘Back to a Healthy Society’ (BASE) was developed.The BASE project aimed to reconnect older adults to society through engaging them in low profile regular physical and social activities. For that a peer-to-peer change-agent approach was designed and applied, in which trained sport and/or health professionals trained older volunteers/peers. These active older volunteers became so-called Neighbourhood Buddies who organised, assisted, and facilitated easily accessible physical and social activities in their neighbourhood to reintegrate and empower older adults who have not been as active so far. Eight partners from six EU countries (DE, NL, PT, MK, LT, ES) exploited a two-step activation process in four local communities (Malaga, Drenthe, Skopje, and Kaunas).a)       Active older volunteers are trained as Neighbourhood Buddies for Healthy Lifestyle so that they could empower their older inactive and often socially isolated peers. For their training, a holistic concept of healthy lifestyle was developed to trigger behavioural change and activation.b)       The local change agents were supported by qualified mentors who form part of the local community ecosystem as sport professionals. The mentors were trained to exploit a local community of practice approach to support developing an active neighbourhood setting. They assisted the Neighbourhood Buddies in co-creating applicable and innovative healthy lifestyle initiatives and to anchor them with local community stakeholders across sectors. From there, reaching out to nearby communities was promoted to extend the impact.This practice oriented symposium will contain four presentations covering the following topics:1.       Background and foundation of the BASE programme (Johan de Jong);2.       The co-creation process and structure of the peer-to-peer change agent approach of BASE (Matthias Guett & Harold Hofenk);3.       Results, impact, and learnings of the BASE project in local communities in Spain, Macedonia, Lithuania, and the Netherlands (Iván López-Fernández);4.       Sustainability and future initiatives of BASE (Matthias Guett & Marco Clemente).Acknowledgement: The Erasmus+ BASE project was co-funded by the European Union.Keywords: Older adults, healthy lifestyle, healthy living, peer-to-peer, community-based, social change